Tick-wildlife host-pathogen network interactions in Northern Africa - Marta Rafael; Amalia Segura; Rita Vaz-Rodrigues; David Relimpio; Oscar Rodríguez; Gabriela de la Fuente; Julio Isla; Christian Gortázar; José de la Fuente (PLoS ONE, 2025)
Ticks are hosts and vectors of zoonotic pathogens, posing a critical threat to public health and the conservation of animal host populations, especially in Northern Africa. Tick-host-pathogen interactions are driven by tick spatial distribution and abundance, and the influence of biotic (animal hosts) and abiotic (environmental conditions) factors. The objectives of this study, conducted in the Maamora Forest (Northwest Morocco), were: (i) description of seasonal interactions network between off-host questing ticks and the wild hosts, rabbits (Oryctolagus cuniculus) and addax (Addax nasomaculatus), (ii) analysis of density-dependent and environmental effects in questing and on-rabbit ticks, and (iii) identification of tick-borne pathogens in questing and on-addax ticks. Results showed that questing and on-rabbit ticks (Hyalomma lusitanicum, Rhipicephalus pusillus, and H. aegyptium) presented significant spatial and seasonal differences. Questing ticks were highly abundant in summer, but infestation on rabbits was higher in spring. Spatially, areas with contact between rabbits and ungulates showed the highest tick infestations during summer. Ticks from rabbits were density-dependent and had a positive relationship with questing ticks. Addax was infested by H. lusitanicum ticks. Tick network of interactions resulted in the presence of Coxiella burnetii in both questing and in addax ticks (17–27%), and Rickettsia aeschlimannii in H. lusitanicum questing ticks (4%). These results support that ticks represent a challenge for human and animal health, as well as ecosystems in Northern Africa, emphasizing the need for long-term studies on their network of interactions, seasonal activity patterns, and tick-borne pathogens in wildlife.